HIV risk practices by female sex workers according to workplace - Damacena, Giseli Nogueira; Szwarcwald, Célia Landmann; Souza Júnior, Paulo Roberto Borges de (Revista de saúde pública, 2014)
OBJECTIVE To investigate differences in HIV infection- related risk practices by Female Sex Workers according to workplace and the effects of homophily on estimating HIV prevalence. METHODS Data from 2,523 women, recruited using Respondent-Driven Sampling, were used for the study carried out in 10 Brazilian cities in 2008-2009. The study included female sex workers aged 18 and over. The questionnaire was completed by the subjects and included questions on characteristics of professional activity, sexual practices, use of drugs, HIV testing, and access to health services. HIV quick tests were conducted. The participants were classified in two groups according to place of work: on the street or indoor venues, like nightclubs and saunas. To compare variable distributions by place of work, we used Chi-square homogeneity tests, taking into consideration unequal selection probabilities as well as the structure of dependence between observations. We tested the effect of homophily by workplace on estimated HIV prevalence. RESULTS The highest HIV risk practices were associated with: working on the streets, lower socioeconomic status, low regular smear test coverage, higher levels of crack use and higher levels of syphilis serological scars as well as higher prevalence of HIV infection. The effect of homophily was higher among sex workers in indoor venues. However, it did not affect the estimated prevalence of HIV, even after using a post-stratification by workplace procedure. CONCLUSIONS The findings suggest that strategies should focus on extending access to, and utilization of, health services. Prevention policies should be specifically aimed at street workers. Regarding the application of Respondent-Driven Sampling, the sample should be sufficient to estimate transition probabilities, as the network develops more quickly among sex workers in indoor venues. OBJETIVO Investigar diferenças nas práticas de risco à infecção pelo HIV segundo local de trabalho das mulheres profissionais do sexo e efeitos de homofilia na estimação da prevalência do HIV. MÉTODOS Foram utilizadas informações de 2.523 mulheres recrutadas por Respondent-Driven Sampling em estudo realizado em 10 cidades brasileiras, 2008-2009. Foram incluídas profissionais com 18 anos ou mais de idade. O questionário foi autopreenchido e incluiu perguntas sobre características da profissão, práticas sexuais, uso de drogas, testes periódicos de HIV e acesso aos serviços de saúde. Utilizaram-se testes rápidos para detecção de HIV. As participantes foram agregadas em dois grupos por local de trabalho: pontos de rua ou locais fechados, e.g., boates, saunas e termas. Foram utilizados testes Qui-quadrado de homogeneidade, levando-se em consideração as probabilidades desiguais de seleção, bem como a dependência entre as observações. Os efeitos de homofilia por local de trabalho foram pesquisados na estimação da prevalência do HIV. RESULTADOS As práticas de maior risco ao HIV associaram-se a: trabalhar em pontos de rua, menor nível socioeconômico, baixa cobertura de exame preventivo de câncer de colo de útero, elevado consumo de crack, maior prevalência de cicatriz sorológica de sífilis e maior prevalência de infecção pelo HIV. O efeito de homofilia foi maior entre as profissionais de locais fechados. Contudo, não afetou a estimativa da prevalência de HIV, mesmo utilizando o procedimento de pós-estratificação por local de trabalho. CONCLUSÕES Os resultados indicaram que as estratégias devem ser dirigidas à ampliação do acesso e à utilização dos serviços de saúde. As políticas de prevenção devem priorizar as profissionais de rua. Em relação à aplicação do Respondent-Driven Sampling, a amostra deve ser suficiente para estimação das probabilidades de transição, uma vez que a rede se desenvolve mais rapidamente entre as profissionais de locais fechados.